Produto interno e ortogonalidade - Lima e Souza, Paulo Rafael de (2015)
In this paper, we consider the vector inner product of a vector space with special applications in high school through concepts such as matrices, Linear Systems and Vector Operations in ℝ² and ℝ³. We also verified linear operators characteristics defined by orthogonal projections. We have also established relationships between vectors and matrices formed by ℝ² bases in order to improve and strengthen the knowledge of primary school teachers, providing them with more certainty and clarity to teach their classes, but also seek to encourage teachers to update and make with their students be motivated for higher education in areas that mathematics, in particular, Linear Algebra is present. Knowing the definition of domestic products and vector spaces, we believe that the teacher can better understand the techniques and algebraic operations the content taught by him. We believe that not aware of this algebra structure, makes the teacher expose a limited way and without further motivation, in terms of other studies by students in high school, and of course, that this view or this approach is not interesting; is necessary to improve the vision in the classroom, it is necessary that the teacher has a panoramic view of what he teaches. Thus, we intend to work with this present domestic product concepts and vector spaces exposing them in a didactic way, showing that somehow is associated with the concepts studied in basic education through applied exercises.